DETERMINATION OF PHENOLIC COMPOUNDS IN “AS-BOG‘IM” AND “AS-QUVVAT” FOOD SUPPLEMENTS - Ziyoda Q. Axmedova (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
The present study is devoted to the quantitative determination of phenolic compounds in “AS-BOG‘IM” and “AS-QUVVAT” food supplements using High-Performance Liquid Chromatography (HPLC). Phenolic compounds are biologically active substances known for their strong antioxidant and anti-inflammatory properties. They play a crucial role in maintaining human health by supporting cardiovascular function, enhancing immune response, promoting cellular regeneration, and reducing oxidative stress. The analysis revealed that “AS-QUVVAT” contains high amounts of salicylic acid (36.753 mg/100 g), quercetin (27.263 mg/100 g), and apigenin (88.300 mg/100 g). In contrast, “AS-BOG‘IM” is rich in kaempferol (55.263 mg/100 g), quercetin (14.583 mg/100 g), and rutin (14.770 mg/100 g). These compounds are known to regulate inflammatory processes, modulate immune cell activity, and protect cells from oxidative damage. The findings indicate that both supplements are valuable sources of natural phenolic compounds with significant pharmacological potential. However, excessive intake of phenolic compounds may lead to toxic effects; therefore, their controlled consumption is essential.